Emotional Regulation Strategies as a Means to Develop Emotional Intelligence Among Madrasah Ibtidaiyah Students - Burniat, Burniat; Eva Sunarya; Eka Lindayati; Dwi Noviani (CV. Creative Tugu Pena, 2025)
This study aims to identify and analyze effective emotional control strategies to improve students' emotional intelligence in Islamic elementary schools. Emotional intelligence is an important skill that influences students' social interactions and academic achievement. The method used in this study is a qualitative approach with data collection techniques through observation and interviews. The research subjects consisted of students in Islamic elementary schools. The results of the study indicate that the implementation of emotional control strategies, such as self-awareness training, relaxation techniques, and effective communication, can help students recognize and manage their emotions better. In addition, an emotional intelligence development program integrated into the school curriculum has also been shown to improve students' ability to interact positively with peers and teachers. This study concludes that good emotional control contributes significantly to improving students' emotional intelligence, which in turn can support their social and academic development. Recommendations for the implementation of these strategies are expected to serve as a reference for educators in creating a learning environment that is more supportive of students' emotional development